Seeking an African Community Approach to Theological Research. Issue 1 (22nd July 2021) - Ibhakewanlan, John-Okoria
Abstract : This response to Ernst Wolff's "South African Universities and the Question of Decolonisation" is under five headings. Regarding the field of academic philosophy, this author insists on a unique African theology. On the role of Western legacy, this piece broadens Wolff's approach in terms of how Western philosophy can commend itself. Thirdly, on the legacy of Africa's colonial heritage, it denounces colonialism but argues against a simple Afro-centrism. On the issue of "relevance, " the tenability of Wolff's view is questioned in the search for an African research methodology. The final point about who may legitimately speak is acknowledged as thorny. In conclusion, this response argues that Africa's history is human history and recalls the need to distinguish between the "roots" and "routes" of African discourse. While the debate rages, this author proposes that the academy adopt an African Community-Based research (ACBR) methodology based on the guiding principle of Knowledge Diffusion.